Pengaruh Rasio Step pada Sudden Enlargement Channel terhadap Heat Flux Kondensasi di Porous Media - Praswanto, Djoko Hari; Siswanto, Eko; Hamidi, Nurkholis (Jurnal Rekayasa Mesin, 2017)
One of the most significant parameter in air conditioning problems is air humidity. A porous media can be used as a heat exchanger component in order to increase the heat transfer performance which is significantly depends on the heat flux values inside of them. To determine the heat flux value, a following test section was modeled in this research. A vapor passed through a channel whereas a particular porous media made of active carbon acted as its heat exchanger media. However, the sudden enlargement at the inlet of channel could affect the homogeneity of temperature distributions and also caused some several turbulencies. The research method is vapor flowed over the porous media for 60 minute with temperature of 300oC.The vapor velocity is varied from 1 m/s to 3 m/s and the step ratio also varied between 0 until 1.66. From the experiment shows the bigger step ratio and vapor velocity results the bigger heat flux and air humidity after passed through the low porous media. Heat transfer was occured in porous media including convection heat transfer with the value of Gr/Re2 smaller than 1.